Red and White Meat of Tuna (Euthynnus affinis); Their Biochemical Role and Nutritional Quality - MUKUNDAN, M K; JAMES, M ARUL; RADHAKRISHNAN, A G; ANTONY, P D (Fishery Technology, 2017)
The biochemical and nutrient compositions of red and white meat of tuna are reported.Based on the data the biochemical role and nutritional quality of red and white meatare discussed. The results show that red meat is adapted for slow and continuousactivity and white meat for quick but occasional activity. In spite of comparatively low lysine content the red meat is adjudged more nutritious than white meat.